The use of anatomical models for learning anesthesia techniques in oral surgery - JVS Canellas; M M Araujo; JPA Arce (Wolters Kluwer Medknow Publications, 2013)
Aim: The objective of this work is to present a new collaborative method for teaching administration of anesthetic block in dentistry, with three-dimensional anatomical models used to improve learning and thereby increase safety, reduce anxiety, and improve the performance of students during the administration of anesthesia in the patients. Materials and Methods: Three-dimensional (3D) models of skulls were made that reproduced all innervations of the V th cranial nerve (trigeminal nerve), as well as some blood vessels, glands, and muscles of mastication. For teaching the local anesthetic techniques we prepared pictures and videos of the administration of anesthesia in the models , which were presented to 130 students in two universities in Brazil. With the help of the models the students could follow the path of the nerves to be anesthetized and identify the anatomical points of reference for the correct positioning of the needle in the tissues. After the presentation the students answered a questionnaire aiming to assess the effect of the 3D models on learning. Results: Eighty-eight percent of students rated the material as excellent, 12% as good, 0% as regular, and 0% as bad (unnecessary materials). After the presentation, 70% of the students felt confident about being able to achieve the nerve block in patients. Conclusion: When exposed to an appropriate method, students recognized the importance of knowledge of anatomy for learning local anesthetic techniques. This method improved the quality of education and increased patient safety during the first injection.